Major adverse kidney events among chronic kidney disease patients with vitamin D deficiency - Lin, Yu-Min; Kao, Chia-Li; Hung, Kuo-Chuan; Liu, Ting-Hui; Yu, Tsung; Liu, Mei-Yuan; Wu, Jheng-Yan; Tsai, Chi-Lun (Frontiers in Nutrition, 2025)
ObjectiveThis study aimed to evaluate the association of vitamin D deficiency (VDD) and major adverse kidney events (MAKEs) among patients with chronic kidney disease (CKD).MethodsWe conducted a retrospective cohort study using the TriNetX Global Collaborative Network. Eligible participants were adults with CKD who had a vitamin D testing between January 01, 2010 and January 31, 2025. According to the status of vitamin level, individuals were classified into two groups, VDD group and control group. Propensity score matching (PSM) was applied to balance baseline characteristics between groups. The primary outcome was the risk of MAKEs during one-year follow-up, while secondary outcomes included all-cause mortality and all-cause hospitalization.ResultsAfter PSM, 29,654 patients were included in each group. The VDD group was associated with a higher risk of MAKEs (hazard ratio [HR], 2.24; 95% confidence interval [CI], 2.08–2.41; p < 0.001). Stratified analyses revealed consistent relationship across multiple subgroups. Additionally, the VDD group was also associated with higher risks of all-cause mortality (HR, 1.92; 95% CI, 1.82–2.02; p < 0.001), and all-cause hospitalization (1.19; 95% CI, 1.14–1.25; p < 0.001).ConclusionVDD in patients with CKD is associated with a significantly higher risk of MAKEs. The finding suggests that VDD may contribute to worse adverse kidney events and highlight the importance of vitamin D status in the clinical management.